2015
DOI: 10.1089/ped.2014.0423
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Resistance in Kawasaki Disease

Abstract: Background: The aim of this study was to identify risk factors for immunoglobulin resistance, including clinical symptoms such as arthritis and the pH of intravenous immunoglobulin. Methods: The data of children with Kawasaki disease who had received immunoglobulin were evaluated. Data regarding the brand of immunoglobulin administered were abstracted from the pharmacy records. Results: Eighty consecutive children with Kawasaki disease were evaluated (Mdn age = 28 months, 66% male). The prevalence of immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
8
0
2
Order By: Relevance
“…In a remarkable fashion, one patient presented with a biphasic pattern, earlyonset arthritis was followed by late-onset arthritis, as already been reported by Duzova et al 11 It has been suggested that arthritis in KD might lead to a worse outcome 7,10 because it indicates a more intense inflammatory response, 2 accounting for some of the first-line therapy resistance. 5 However, Gong et al did not find any association between the articular involvement and worse prognosis or higher inflammatory response. 2 Curiously, we found higher haemoglobin levels at admission in patients with arthritis, a finding also noted by Gong et al 2 We acknowledge that this may be due to the fact that haemoglobin level is influenced by age, with higher levels in older children.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a remarkable fashion, one patient presented with a biphasic pattern, earlyonset arthritis was followed by late-onset arthritis, as already been reported by Duzova et al 11 It has been suggested that arthritis in KD might lead to a worse outcome 7,10 because it indicates a more intense inflammatory response, 2 accounting for some of the first-line therapy resistance. 5 However, Gong et al did not find any association between the articular involvement and worse prognosis or higher inflammatory response. 2 Curiously, we found higher haemoglobin levels at admission in patients with arthritis, a finding also noted by Gong et al 2 We acknowledge that this may be due to the fact that haemoglobin level is influenced by age, with higher levels in older children.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that arthritis in KD might lead to a worse outcome because it indicates a more intense inflammatory response, accounting for some of the first‐line therapy resistance . However, Gong et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al [44] suggested that clinical features cannot predict IVIG-resistant Kawasaki disease; however, this study found that changes in oral mucosa, cervical lymphadenopathy, swelling of extremities, and polymorphous rash can predict IVIG-resistant Kawasaki disease, whereas conjunctival congestion cannot. Hartas et al [15] showed that patients with Kawasaki disease who also have acute arthritis are at high risk for being IVIG-resistant, but because of the lack of relevant studies, we did not include this factor in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As guidelines mais recentes 5 recomendam a administração de uma segunda dose de IgEV (pelo seu efeito anti-inflamatório cumulativo) ou a administração de pulsos de corticoide em alta dose (preferencialmente metilprednisolona 20-30 mg/kg, durante três dias, com ou sem um curso subsequente de prednisolona oral). Estes pacientes, pelo fenótipo "hiperinflamatório" subjacente e continuado, apresentam maior risco de desenvolverem aneurismas coronários e complicações, 8,9,18,19 pelo que diversos sistemas de pontuação e preditores têm vindo a ser investigados no sentido de identificar precocemente este grupo de pacientes, permitindo um tratamento adjuvante anti--inflamatório mais agressivo numa fase inicial. O score de Harada, desenvolvido no Japão em 1991, foi primeiro sistema de pontuação criado, inicialmente visando identificar as crianças com maior risco de AAC que seriam selecionadas para a administração de IgEV, nessa altura com disponibilidade limitada.…”
Section: Discussionunclassified